Investigation of the velocity field downstream of a benchmark vent using numerical simulation and hot-wire anemometry - Šíp, Jan; Lízal, František; Elcner, Jakub; Pokorný, Jan; Jícha, Miroslav (EDP Sciences, 2018)
The velocity field in the area behind the automotive vent was measured by hot-wire anenemometry in detail and intensity of turbulence was calculated. Numerical simulation of the same flow field was performed using Computational fluid dynamics in commecial software STAR-CCM+. Several turbulence models were tested and compared with Large Eddy Simulation. The influence of turbulence model on the results of air flow from the vent was investigated. The comparison of simulations and experimental results showed that most precise prediction of flow field was provided by Spalart-Allmaras model. Large eddy simulation did not provide results in quality that would compensate for the increased computing cost.

The velocity field in the area behind the automotive vent was measured by hot-wire anenemometry in detail and intensity of turbulence was calculated. Numerical simulation of the same flow field was performed using Computational fluid dynamics in commecial software STAR-CCM+. Several turbulence models were tested and compared with Large Eddy Simulation. The influence of turbulence model on the results of air flow from the vent was investigated. The comparison of simulations and experimental results showed that most precise prediction of flow field was provided by Spalart-Allmaras model. Large eddy simulation did not provide results in quality that would compensate for the increased computing cost.
Investigation of the velocity field downstream of a benchmark vent using numerical simulation and hot-wire anemometry
Keywords: Automotive vent; Constant temperature anemometry; Numerical simulation; Automotive vent; Constant temperature anemometry; Numerical simulation